ANALISIS MANUFACTURING CYCLE EFFECTIVENESS (MCE)UNTUK MENINGKATKAN COST EFFECTIVE DANMENGURANGI NON VALUE ADDED: (STUDI KASUS PADA PT. IMA MONTAZ SEJAHTERA- LHOKSEUMAWE) - Yunita, Nur Afni; Ulfa, Cut Nurlaila (Jurnal Akuntansi dan Keuangan, 2018)
This study aims to analyze the size of the effectiveness of the production process or known as manufacturing cycle effectiveness (MCE) to increase cost effective and reduce non valueadded activity at PT. Ima Montaz Sejahtera- Lhokseumawe. The research method used is Mix Method, which combines quantitative data analysis method and qualitative descriptive analysis with a case study approach. Data collection is conducted by interviews and documentation studies. The result show that MCE is 56,36%. The MCE size shows that there are still non value added activities that occur in the production process, so the management of PT. Ima montaz Sejahtera can plan a reduction program for non value added activity.